Experimental study on the performance of shield tunnel tail grout in ground - Jiaxin Liang; Wei Liu; Xinsheng Yin; Wentao Li; Zhe Yang; Jichen Yang (Underground Space, 2025)
Shield tail grouting is an important measure to control tunnelling-induced ground deformation by injecting prepared grouting materials to fill the tail gap. The working performance of grout is usually invisible and hard to obtain in construction. This paper carries out an experimental study to investigate the tail grout behavior in ground. In the current research, a testing device is developed to explore the grout behavior in varying soils. The grout working performance is evaluated not only by the liquid grout properties such as fluidity, consistency, bleeding rate, stone rate and compressed deformation but also solid grout properties such as unconfined compressive strength and permeability. Three typical grouts are chosen and their behaviors in the various soils are observed. To take an insight on the behaviors, scanning electron microscopy and mercury intrusion porosimetry analysis are employed. The microstructure of solid grout is a sign of its working performance. The observation shows that the solid grout micro-structure is influenced by grout proportions, pressure, and ground permeabilities. The experimental results are applied in the case of Beijing Metro Line 12 for validation and as a result, the ground movement is inhibited due to high performance of tail grout.